Super goal - Santos, Manuel dos (McGraw-Hill, 2001)
An American English series specially designed for teenagers and young adults that takes students from absolute beginning to the high-intermediate level. It integrates the 4 skills of speaking, listening, reading and writing. It puts an emphasis on using grammar in communicative activities.